The Effects of Angry Expressions and Fearful Expressions on Duration Perception: An ERP Study - Yin, Huazhan; Cui, Xiaobing; Bai, Youling; Cao, Gege; Zhang, Li; Ou, Yuhong; Li, Dan; Liu, Jinping (Frontiers in Psychology, 2021)
Little is known about the electrophysiological basis of the effect of threat-related emotional stimuli with different motive directions on interval judgment. Thus, event-related potentials were employed to examine the effects of two threat-related emotional expressions (angry expressions and fearful expressions) on the judgment of intervals in the range of 490–910 ms. Behavioral results showed that there was a greater underestimation of the duration of angry expressions than fearful expressions (i.e., the generalization gradient for the angry expressions was shifted to the right more than for the fearful expressions) when compared with neutral expressions. Event-related potentials results showed that, compared with neutral expressions, a smaller area of contingent negative variation (an online event-related potentials index of timing) was observed in fearful expression conditions and was more apparent in the angry expression condition (angry expression = 1.87±.13μV•s; fearful expression = 2.24±.15μV•s; and neutral expression = 2.69±.15μV•s). The results revealed that precise neural mechanisms may underlie the attention effects of different subtypes of threat-associated emotions on interval judgment; compared with neutral expressions, angry expressions are likely to distract more attentional resources from timing than fearful expressions. The chief contribution of the current study is that it provides neural correlates of the difference between angry expressions and fearful expressions on interval judgment, and demonstrates beyond the behavioral level that the categorization of threat-related emotions should be refined so as to highlight the adaptability of the human defense system.